Nilai-nilai Islam dalam pantun Melayu : analisis pantun utara dalam buku Kurik Kundi Merah Saga - Mohd Fairus, Abd Majid (2017)
The book of poem (pantun), Kurik Kundi Merah Saga (KKMS) offers a set of Malay pantun from various places in the peninsula, Sabah and Sarawak. Pantun contained in this book have various aspects of the Malays and Islam that can serve as role models to the community. The content of the pantun infuses the traditional values of Islam, which makes KKMS northern region pantun precious and special. However, the truthfulness and accuracy of the Islamic values in KKMS with the teaching of Islam have yet to be identified. The present study examines the Islamic values of KKMS northern region pantun such as beliefs, practices and ethics, which have not been studied thoroughly in the previous studies. Therefore, this study was conducted to investigate the values of Islam in KKMS northern region pantun with three objectives; to examine the Islamic form of KKMS northern region Malay pantun, to categorize KKMS northern region Malay pantun based on Islamic values and to analyze KKMS northern region Malay pantun based on beliefs, practices and ethics of Islam. The present study used qualitative methods i.e., archival research and content analysis. Data were analyzed based on the content of the pantun and the use of the terms in the pantun. Based on the findings, it can be concluded that most of the KKMS northern region Malay pantun, incorporate Islamic values in a clear and comprehensive manner. The study found that there are eight (8) significant Islamic values applied in terms of trust, six (6) Islamic values in terms of practice, and 30 Islamic values in terms of ethics. However, the most dominant value of Islam in the pantun is ethics. The study shows that the Malay traditional society uses pantun as a channel of da’wah and guidance in life. Dominant Islamic values in terms of ethics indicate that the Islamic pattern of moral values strongly influence the establishment of the morals of the Malay community. The results of the study reflect clearly the Islamic values among the Malays as manifested in the pantun